Elevated Circulating LINC-P21 Serves as a Diagnostic Biomarker of Type 2 Diabetes Mellitus and Regulates Pancreatic β-cell Function by Sponging miR-766-3p to Upregulate NR3C2 - Cao, Zhibin; Yao, Fuwang; Lang, Yuqin; Feng, Xueqiang (Experimental and Clinical Endocrinology & Diabetes, 2020)
Objective The purpose of this study was to evaluate the clinical value and biological function of long non-coding RNA (lncRNA) LINC-P21 in type 2 diabetes mellitus (T2DM), and explore the underlying mechanisms.Methods The expression of LINC-P21 was estimated using quantitative real-time PCR. The functional role of LINC-P21 was explored by gain- and loss-of-function experiments. INS-1 cell proliferation was analyzed using a cell counting kit-8 (CCK-8)assay, and the glucose-stimulated insulin secretion was measured using an ELISA kit. The miRNAs that might be sponged by LINC-P21 were analyzed, and the subsequent target genes were predicted and assessed in INS-1 cells.Results Serum expression of LINC-P21 was elevated in T2DM patients, which was correlated with fasting blood glucose levels and disease diagnosis. The glucose-stimulated insulin secretion and the proliferation of INS-1 cells were enhanced by LINC-P21 knockdown, but the overexpression of LINC-P21 led to opposite effects. miR-766-3p could be directly inhibited by LINC-P21 in INS-1 cells and reverse the effects of LINC-P21 on β-cell function. Additionally, NR3C2 was determined as a target of miR-766-3p, which could be positively regulated by LINC-P21 and had same effects with LINC-P21 on INS-1 cell proliferation and insulin secretion.Conclusion All the data demonstrated that serum elevated LINC-P21 and decreased miR-766-3p serve as candidate diagnostic biomarkers in T2DM patients. LINC-P21 acts as a potential regulator in insulin secretion and proliferation of pancreatic β-cells through targeting miR-766-3p to upregulate NR3C2.
Keywords: Type 2 diabetes mellitus; LINC-P21; MicroRNA-766-3p; NR3C2; Pancreatic β-cell; Proliferation